Análisis de la Ley del Bodeguero N°30877 como fuente de competitividad de las bodegas de la urbanización Los Cedros de Villa - Chorrillos: 2022 - Guerra Rodríguez, Linet Briggitte (2023)
The objective of this research work is to determine the relationship between the Ley del bodeguero N° 30877 and the competitiveness of the wineries in Cedros de Villa, a traditional and residential urbanization located in the district of Chorrillos during the year 2022. The research was developed under a quantitative approach, correlational level and non-experimental design, where 133 winemakers in the area were taken as a study sample, all of them correctly formalized and located in Cedros de Villa. A questionnaire was used as a research instrument. When the results were analyzed, they were obtained thanks to the application of Sperman's Rho, which yielded a correlation of 0.771, which shows a high correlation between the variables. This allows us to affirm that the dimensions of brand competitiveness, seller competitiveness and brand innovation are related to the strategic plan applied by the Municipality of Chorrillos on the Ley del Bodeguero.